1981
DOI: 10.1002/hep.1840010503
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus DNA in the sera of HBsAg carriers: A marker of active hepatitis B virus replication in the liver

Abstract: Sera and liver biopsies from 30 Italian patients, carriers of HBsAg for at least 3 years, were examined for markers of hepatitis B virus (HBV) infection by serological assays and immunofluorescence. Biopsies were analyzed for HBcAg, HBsAg, and delta antigen by immunofluorescence; sera were assayed for HBsAg/anti-HBs, HBcAg/anti-HBc, HBeAg/anti-HBe, delta/anti-delta, HBV-specific DNA polymerase activity and the presence of HBV DNA. HBcAg, HBeAg, and DNA polymerase tests were positive in the sera of 71, 86, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(110 citation statements)
references
References 33 publications
8
102
0
Order By: Relevance
“…Furthermore, our findings confirm and expand results of investigations using the conventional hybridisation assay for the detection of HBV DNA. These earlier studies showed that viral replication, as demonstrated by the presence of viral DNA in the circulation, is correlated with the presence of HBeAg and with symptomatic liver disease [Bonino et al, 1981;Berninger et al, 1982;Scotto et al, 1983;Zyzik et al, 19861. Our data fit well into this pattern. All HBeAg-positive individuals tested were indeed also DNA positive, although they were apparently asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our findings confirm and expand results of investigations using the conventional hybridisation assay for the detection of HBV DNA. These earlier studies showed that viral replication, as demonstrated by the presence of viral DNA in the circulation, is correlated with the presence of HBeAg and with symptomatic liver disease [Bonino et al, 1981;Berninger et al, 1982;Scotto et al, 1983;Zyzik et al, 19861. Our data fit well into this pattern. All HBeAg-positive individuals tested were indeed also DNA positive, although they were apparently asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatitis B e antigen (HBeAg) is a clearly better but also indirect marker for the presence of virus in the blood. By far the best diagnostic parameter in this respect is the viral DNA, which can be detected by a sensitive direct hybridisation assay [Bonino et al, 1981;Berninger et al, 19821. The introduction of this test was one of the major improvements for the diagnosis of hepatitis B.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the early 1980s it became apparent that HBV could replicate in the absence of HBeAg. [4][5][6] Patients from the Mediterranean area, although negative for HBeAg and positive for antibodies to HBeAg (anti-HBe), were reported to have CHB with replicating HBV. 7 The term anti-HBe-positive or HBeAgnegative CHB was then proposed 4 and subsequently became widely accepted.…”
mentioning
confidence: 99%
“…The following connections have been found. (i) When hepatitis B e antigen (HBeAg), which is part of HBcAg (Ohori et al, 1979; Mackay et al, 1981), is detectable in serum, Dane particles, HBV-specific DNA polymerase and DNA are demonstrable in the serum (Nordenfelt & Kjellen, 1975;Imai et al, 1976;Ohori et al, 1980) and HBcAg and HBV DNA in liver tissues (Bonino et al, 1981;Hadziyannis et al, 1983). (ii) The localization of HBcAg in hepatocytes varies even in the same tissue (Gudat et al, 1975;Yamada & Nakane, 1977; Huang & Neurath, 1979).…”
mentioning
confidence: 99%